Exploration of the lower threshold of iodine intake in Southern Chinese young adults based on 'overflow theory' in an iodine balance study. - Wang, Jun; Zhang, Hongmin; Mao, Deqian; Tan, Hongxing; Yu, Wei; Xu, Jian; Hong, Wenxu; Piao, Jianhua; Yang, Lichen; Liu, Xiaobing; Lu, Jiaxi; Li, Weidong; et al. (Nutrition Journal, 2022)
Background: Appropriate iodine intake for adults is essential to reduce the prevalence of thyroid diseases, but there is little research data on iodine requirement of Chinese population. This study aimed to explore the iodine requirement of young adults to maintain a healthy status based on 'overflow theory'.Methods: Iodine-balance experiment has been performed in this project. We conducted an 18-day study consisted of a 6-day acclimation period and 3 consecutive experimental stages in 37 Chinese healthy young adults (23 female and 14 male). Each stage was consumed for 4 days. Strictly-controlled low-iodine intake diets were provided for adults in the first period, an egg or 125mL milk was added in the second and third period, respectively. The dietary samples, 24-h urine specimens and faeces of volunteers were collected daily for assessment of iodine intake and excretion in volunteers.Results: Mean values of iodine intake (22.7±3.6, 35.1±3.7, and 52.2±3.8μg/d), excretion (64.7±13.9, 62.3±12.6, and 94.3±14.5μg/d) and iodine balance (-35.2±19.5, -21.0±19.8, and -33.5±26.9μg/d) were significantly different among three periods for male (P<0.001 for all); mean values of iodine intake (16.6±3.1, 29.7±2.7, and 48.0±2.7μg/d), and excretion (47.0±9.9, 55.5±8.1, and 75.7±12.4μg/d) were significantly different among three periods for female (P < 0.001 for all). No significant difference was observed among the 3 periods for female in the iodine balance (-30.5±9.3, -25.9±7.3, and -27.6±12.1μg/d). The linear regression equation of iodine excretion on iodine intake was Y=0.979X+37.04 (male) and Y=0.895X+31.48 (female). Compared with stage 2, iodine excretion increments in stage 3 had exceeded the iodine intake increment for men. The ratio of increment was 1.675 for male when the average iodine intake was 52.2μg/d in stage 3. When the iodine excretion increment equaled to the iodine intake increment, the daily iodine intake of men was 47.0μg.Conclusion: We have evaluated the iodine requirement of young adults in southern China based on overflow theory. Our results indicate the lower limit of iodine requirement for Chinese young men is 47.0μg/d. The trial was registered at www.chictr.org.cn as ChiCTR1800014877.